PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP PRODUKTIVITAS KARYAWAN PT TRAKINDO UTAMA SITE LATI DI KABUPATEN BERAU: PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP PRODUKTIVITAS KARYAWAN PT TRAKINDO UTAMA SITE LATI DI KABUPATEN BERAU - Yulita Maria (ECO-BUILD, 2022)
The purpose of the research conducted to determine and analyze the influence of Occupational Safety and Health (K3) of employees at PT Trakindo Utama Site Lati in Berau Regency. The unit of analysis in this study were all employees at PT Trakindo Utama Berau Site Lati. The population was 71 participants as the research sample , so the researcher utilized the entire population as a research sample. Non-probability sampling with saturated sample methodology is the sampling technique that employed when samples of the entire population are acquired. With the involvement of the SPSS Version 21 application program, multiple linear regression was used as the analytical method in this study. According to the results of a study, it can be seen that there is a significant and positive influence between occupational safety and occupational health on employee productivity of PT Trakindo Utama Site Lati in Berau Regency as shown by the correlation coefficient of 0.635 or 63.5%. This indicates that whereas other factors influence the remaining 36.5% of employee productivity, occupational safety and health (K3) affects employee productivity by 63.5%. Thus, the hypothesis was acceptable.